2021
DOI: 10.1016/j.heliyon.2021.e07051
|View full text |Cite
|
Sign up to set email alerts
|

Parents willingness to vaccinate their daughter against human papilloma virus and its associated factors in Bench-Sheko zone, southwest Ethiopia

Abstract: Background: In Ethiopia, the human papillomavirus vaccine has been introduced since 2018. Since the vaccination program targets girls age 9-13, the success of vaccination depends on the parental decision and their willingness to vaccinate their daughters. Therefore, a study on parental willingness to vaccinate their daughter and factors associated is needed. Objective: To assess parent's willingness to vaccinate their daughter against the human papillomavirus and its associated factors in Bench-Sheko Zone, sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
41
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(57 citation statements)
references
References 25 publications
14
41
2
Order By: Relevance
“…The principal finding of this study showed that although the participants of the study had limited knowledge about HPV vaccine, majority of individuals were willing to vaccinate their child. This acceptance rate was consistent with the study findings of Nigeria (88.9%) [17], and Tanzania (93%) [21], but higher than rates noted in a South African (80%) study [12], Gondar (Northern Ethiopia) study (81.3%) [10], and Bench-Sheko zone, south-west Ethiopia (79.5%) study [15]. The highest vaccine acceptance rate in the present study could be partly due to the current national campaign for HPV vaccination in Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The principal finding of this study showed that although the participants of the study had limited knowledge about HPV vaccine, majority of individuals were willing to vaccinate their child. This acceptance rate was consistent with the study findings of Nigeria (88.9%) [17], and Tanzania (93%) [21], but higher than rates noted in a South African (80%) study [12], Gondar (Northern Ethiopia) study (81.3%) [10], and Bench-Sheko zone, south-west Ethiopia (79.5%) study [15]. The highest vaccine acceptance rate in the present study could be partly due to the current national campaign for HPV vaccination in Ethiopia.…”
Section: Discussionsupporting
confidence: 89%
“…Four hundred thirty (430) samples were estimated by using single population proportion formula by taking 95% confidence interval, 4% margin of error, 79.5% proportion of HPV vaccine acceptance in Bench-Sheko zone, south-west Ethiopia [ 15 ] and adding up 10% non-response rate. Two-stage sampling technique was employed to recruit the participants for the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though Ethiopian women are willing to vaccinate their children for HPV 54,55 still there are challenges that affect its effective utilization. Ineffectiveness of the recently provided vaccine (HPV2 and HPV4) for other prevalent strains of HPV (HPV‐52, 56,57 HPV‐56, 57,58 HPV‐58, 57 and HPV‐31 57 ) in Ethiopia, high vaccine costs, inadequate delivery system, and lack of community involvement to create awareness about CC and early screening tools are challenges that hinder effective utilization HPV vaccination in Ethiopia 31,40,59–61 .…”
Section: Discussionmentioning
confidence: 99%